Passion, knowledge and motivation: ontologies of desire - Linstead, Stephen; Brewis, Joanne (2007)
In this paper we address some neglected ontological issues regarding the ideas of passion and knowledge in the contemporary Western context. We argue that passion as a concept can be understood in two main ways. The prevalent interpretation in organization studies is telelogical, that of a powerful, purposive motivation to achieve an end result. The second is an ontological understanding of the nature of desire, which in itself is double-sided. Using the ideas of Foucault and Bataille, we suggest desire can be read as lack but also-alternatively as a free-flowing creative force operating behind the quest for knowledge. Through the power effects of discourses like knowledge management and motivation theory, this flow of desire is curtailed in its ability to make meaning through non-knowledge as well as knowledge. This entails that formless, unpredictable desire is discursively condensed into functional motivation, whilst at the same time the protean, curious urge to connect to the externality of the world becomes structured into the instrumental, conservative management of knowledge. We reflect here on both of these discursive trajectories, as well as on some of their implications. - Reproduced.
Keywords: Motivation